The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5397/cise.2014.17.1.25
|View full text |Cite
|
Sign up to set email alerts
|

In vivo 3D Kinematics of Axis of Rotation in Malunited Monteggia Fracture Dislocation

Abstract: Background: Normal elbow joint kinematics has been widely studied in cadaver, whilst in vivo study, especially of the forearm, is rare. Our study analyses, in vivo, the kinematics of normal forearm and of malunited forearm using a three-dimensional computerized simulation system. Methods: We examined 8 patients with malunited Monteggia fracture and 4 controls with normal elbow joint. The ulna and radius were reconstructed from CT data placing the forearm in three different positions; full pronation, neutral, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…First, screw axis, which is determined in terms of rotation around and translation along one unique axis, i.e., the 3D deformity axis, using the screw displacement axis technique, was calculated during flexion, and we defined it as the axis of rotation (AOR). 4,5) Movements of AOR during flexion in groups were compared. We then calculated the rotational axis of the ulno-humeral joint in the position from full extension to full flexion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, screw axis, which is determined in terms of rotation around and translation along one unique axis, i.e., the 3D deformity axis, using the screw displacement axis technique, was calculated during flexion, and we defined it as the axis of rotation (AOR). 4,5) Movements of AOR during flexion in groups were compared. We then calculated the rotational axis of the ulno-humeral joint in the position from full extension to full flexion.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] However, a few studies have reported the use of 3D imaging in the upper extremity, including the hand and elbow. 4,5) In general, if patients with nonunion of the lateral humeral condyle fracture have no symptoms, there is no need for surgical treatment. However, nonunion of the lateral humeral condyle fracture combined with cubitus valgus deformity and instability often results in pain in the elbow, along with ulnar neuropathy and cosmetic problems.…”
Section: Introductionmentioning
confidence: 99%